Fracture Response of Girth-Welded Pipeline With Canoe Shape Embedded Crack Subjected to Large Plastic Deformation - Lie, Seng Tjhen (2017)
Long-distance offshore pipelines always suffer large plastic deformation during installation and operation. Accompanied by high internal pressure, potential flaws are found to initiate from the girth welds, and this brings a significant challenge to the structural integrity of the pipelines. The currently used procedures for fracture assessment of pipelines are usually stress based, which are unsuitable for application to cracked pipeline subjected to large plastic deformation. Therefore, the aim of this paper is to investigate the fracture assessment of pipeline subjected to large plastic deformation and identify and understand the critical parameters influencing the fracture responses under actual loading conditions. The evolution of crack tip opening displacement (CTOD) of a pipeline segment with an embedded canoe shape crack located in the middle of the girth weld is investigated under pure bending and biaxial loading through 3D elastic–plastic finite-element simulations. The effects of crack width, crack length, pipeline thickness, material hardening, and internal pressure on fracture response are discussed. Finally, a strain-based failure assessment diagram (FAD) is developed, and comparison between fracture assessment by BS7910:2013 and finite-element simulations concludes that the former produces conservative predictions for deep crack.